Birth weight and blood pressure: 'J' shape or linear shape? Findings from a cross-sectional study in Hong Kong Chinese women. Issue 9 (8th September 2014) - Xie, Yao Jie; Ho, Suzanne C; Liu, Zhao-Min; Hui, Stanley Sai-Chuen
Abstract : Objectives: To investigate the association between birth weight and blood pressure (BP) and to determine the effect of body size change from birth to adulthood on BP. Design: A cross-sectional design to collect retrospective data. Participants: 1253 female nurses aged 35–65 years in Hong Kong. Main outcome measures: Birth weight, height, weight, BP, waist circumference, demographics and lifestyle factors were collected by a self-administered questionnaire through mail survey. These self-reported variables have been validated in a pilot study. The conditional relative weight (CRW), which was calculated as a residual of current weight regressed on birth weight, was used to express higher or lower relative weight gain from birth to adulthood. Results: No significant linear association between overall range of birth weight and BP was found. The curve estimation showed a significant quadratic curvilinear association ('J' shape). In the piecewise-linear analysis, a significant inverse association between birth weight z-scores and BP was observed in the birth weight ≤3.1 kg group (systolic BP (SBP): coefficient B=−1.73, 95% CI −3.17 to −0.30; diastolic BP (DBP): B=−1.12, 95% CI −2.19 to −0.06). A positive but non-significant association occurred in the birth weight >3.1 kg group. Participants who belonged to the lowest 10% birth weight category but at the current top 10% BMI group had higher BP than participants in other BMI groups. The CRW z-score was positively associated with BP (coefficient B: 4.18 for SBP and 2.87 for DBP). Conclusions: Unlike most previous studies, we found a 'J' shape association rather than a linear association between birth weight and BP. Women with large percentile crossing of body size from birth to adulthood were more likely to have elevated BP. A higher weight gain from birth to adulthood than expected led to higher BP.